Descriptive-contrastive analysis of Ilocano and English personal pronouns - Cruz, Bernabela Tomas de la 1927- ([Quezon City s.n.], 1964)
This study aims to present a descriptive-contrastive analysis of Ilocano and English personal pronouns and to predict problems that might be met by Ilocano students in learning English personal pronouns.
Thesis (M.A.T.)--University of the Philippines
Keywords: Iloko language -- Pronoun; English language -- Pronoun